2015
DOI: 10.1007/s00259-015-3004-y
|View full text |Cite
|
Sign up to set email alerts
|

High FDG uptake areas on pre-radiotherapy PET/CT identify preferential sites of local relapse after chemoradiotherapy for locally advanced oesophageal cancer

Abstract: High FDG uptake on pretreatment PET/CT identifies tumour subvolumes that are at greater risk of recurrence after CRT in patients with LAOC. We propose a 60% SUVmax threshold to delineate high FDG uptake areas on initial PET/CT as reduced target volumes for RT dose escalation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
3
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 41 publications
3
30
3
4
Order By: Relevance
“…In different studies, it has been reported that the SUV max values could be used as independent prognostic markers in patients with esophageal cancer [22][23][24][25]. In this study, we hypothesized finding a correlation between the hematological parameters and the quantitative PET parameters, which were previously reported as prognostic factors in several studies.…”
Section: Discussionmentioning
confidence: 78%
“…In different studies, it has been reported that the SUV max values could be used as independent prognostic markers in patients with esophageal cancer [22][23][24][25]. In this study, we hypothesized finding a correlation between the hematological parameters and the quantitative PET parameters, which were previously reported as prognostic factors in several studies.…”
Section: Discussionmentioning
confidence: 78%
“…This study focused on lung cancer, a tumour type for which standard SUV metrics have been proved to be clinically useful [20][21][22][23] and for which quantification of tumour heterogeneity in PET images has recently gained interest [24,25] and aimed at evaluating the potential impact of the EARL accreditation program [5] …”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies investigated the predictive and prognostic role of sequential F-18 FDG PET/CT for metabolic tumor response and survival in LAEC treated preoperatively by CRT and revealed conflicting results [17,18,19,20,21,22,23,24,25,26,27,28]. Most of these studies used the SUV max values for the prediction of metabolic response and survival in LAEC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fathinul Fikri et al [19 ]reported that pretreatment with F-18 FDG PET/CT SUV max of a primary tumor and the presence of FDG-avid lymph nodes independently predict survival in patients with esophageal carcinoma which may potentially be used as surrogate markers of prognostic and therapeutic purposes. Although different threshold values were used, other studies showed that ΔSUV max was associated with survival in LAEC treated preoperatively by CRT [20,21,22,23,24]. Yang et al [22] reported that a decrease of 51% in FDG uptake during chemoradiation was a sensitive and accurate cut point for predicting progression-free survival.…”
Section: Discussionmentioning
confidence: 99%